Best Paper Selection (Yearbook of Medical Informatics, 2018)
Olchanski N, Dziadzko MA, Tiong IC, Daniels CE, Peters SG, O'Horo JC, Gong MN. Can a Novel ICU Data Display Positively Affect Patient Outcomes and Save Lives? J Med Syst 2017;41:171 https://dx.doi.org/10.1007/s10916-017-0810-8Andersen B, Kasparick M, Ulrich H, Franke S, Schlamelcher J, Rockstroh M, Ingenerf J. Connecting the clinical IT infrastructure to a service-oriented architecture of medical devices. Biomed Tech 2018;63(1):57-68 https://www.degruyter.com/doi/10.1515/bmt-2017-0021Plastiras P, O'Sullivan DM. Combining Ontologies and Open Standards to Derive a Middle Layer Information Model for Interoperability of Personal and Electronic Health Records. J Med Syst 2017;41:195 https://link.springer.com/article/10.1007%2Fs10916-017-0838-9Nguyen P, Tran T, Wickramasinghe N, Venkatesh S. Deepr: A Convolutional Net for Medical Records. IEEE J Biomed Health Inform 2017;21(1):22-30 https://dx.doi.org/10.1109/JBHI.2016.2633963